A systems model describing the impact of organic resource use on farming households in low to middle income countries - Smith, J.; Nayak, D.; Datta, A.; Narkhede, W. N.; Albanito, F.; Balana, Bedru; Bandyopadhyay, S.K.; Black, H.; Boke, S.; Brand, A.; Byg, A.; Dinato, M.; et al. (Elsevier, 2020)
We present a new systems model that encompasses both environmental and socioeconomic outcomes to simulate impacts of organic resource use on livelihoods of smallholder farmers in low to middle income countries. It includes impacts on soils, which in many countries are degrading with long term loss of organic matter. Many farmers have easy access to animal manures that could be used to increase soil organic matter, but this precious resource is often diverted to other purposes, such as fuels, also resulting in loss of the nutrients needed for crop production. This model simulates impacts of different management options on soil organic matter turnover, availability of water and nutrients, crop and animal production, water and energy use, labour requirements and household income and expenditure. An evaluation and example application from India are presented and used to illustrate the importance of considering the whole farm system when developing recommendations to help farmers improve their soils.